Multicenter epidemiological survey of pneumatosis intestinalis in Japan - Naoki Ohmiya; Ichiro Hirata; Hirotsugu Sakamoto; Toshifumi Morishita; Eiko Saito; Katsuyoshi Matsuoka; Tadanobu Nagaya; Shinji Nagata; Miyuki Mukae; Koji Sano; Takayoshi Suzuki; Ken-ichi Tarumi; et al. (BMC Gastroenterology, 2022)
Abstract Background Pneumatosis intestinalis (PI) is a rare condition characterized by gas collection in the intestinal wall. We aimed to determine the etiology and affected segments associated with complications, treatment, and outcome. Methods We conducted a multicenter epidemiological survey using a standardized data collection sheet in Japan. Complicating PI was defined as strangulation or bowel necrosis, bowel obstruction, adynamic ileus, sepsis, shock, and massive gastrointestinal bleeding requiring blood transfusion. Results We enrolled 167 patients from 48 facilities. Multivariate analysis revealed that older age (adjusted OR, 1.05 and 95% confidence intervals [CI], 1.02–1.09, P = 0.0053) and chronic kidney disease (adjusted OR, 13.19 and 95% CI 1.04–167.62, P = 0.0468) were independent predictors of the small-bowel-involved type. Complicating PI was associated with the small-bowel-involved combined type (adjusted OR, 27.02 and 95% CI 4.80–152.01, P = 0.0002), the small-bowel-only type (adjusted OR, 3.94 and 95% CI 1.02–15.27, P = 0.0472), and symptomatic PI (adjusted OR, 16.24 and 95% CI 1.82–145.24, P = 0.0126). Oxygen therapy was performed in patients with a past history of bowel obstruction (adjusted OR, 13.77 and 95% CI 1.31–144.56, P = 0.0288) and surgery was performed in patients with complicating PI (adjusted OR, 8.93 and 95% CI 1.10–72.78, P = 0.0408). Antihypertensives (adjusted OR, 12.28 and 95% CI 1.07–140.79, P = 0.0439) and complicating PI (adjusted OR, 11.77 and 95% CI 1.053–131.526; P = 0.0453) were associated with exacerbation of PI. The complicating PI was the only indicator of death (adjusted OR, 14.40 and 95% CI 1.09–189.48, P = 0.0425). Discussion Small-bowel-involved type and symptomatic PI were associated with complications which were indicators of poor prognosis.